Error rate for imputation from the Illumina BovineSNP50 chip to the Illumina BovineHD chip - Schrooten, Chris; Dassonneville, Romain; Ducrocq, Vincent; Brøndum, Rasmus F.; Lund, Mogens S.; Chen, Jun; Liu, Zengting; González-Recio, Oscar; Pena, Juan; Druet, Tom (Genetics Selection Evolution, 2014)
Imputation of genotypes from low-density to higher density chips is a cost-effective method to obtain high-density genotypes for many animals, based on genotypes of only a relatively small subset of animals (reference population) on the high-density chip. Several factors influence the accuracy of imputation and our objective was to investigate the effects of the size of the reference population used for imputation and of the imputation method used and its parameters. Imputation of genotypes was carried out from 50 000 (moderate-density) to 777 000 (high-density) SNPs (single nucleotide polymorphisms).